Does exchange rate misalignments lead changes in macroeconomic fundamentals? - Dybka, Piotr; Rubaszek, Michał (Publishing House of Wroclaw University of Economics and Business, 2024)
This article aimed at verifying the reliability of equilibrium exchange rate (EER) concepts by exploring if exchange rate misalignments are leading to changes in macroeconomic fundamentals. The authors focused on G10 currencies and the three most popular EER models which the IMF regularly uses within the External Balance Assessment: Purchasing Power Parity, Behavioural EER and Fundamental EER. In methodological terms, the study applied the cross-sectional predictability approach developed by Sarno and Schmeling (2014), which ranks countries on the basis of the scale of EER misalignment to check if this ranking helps to predict key macro variables. The results indicate that EER misalignment contains cross-sectional predictive power and allows forecasting real effective exchange rates, short-term interest rates and current account balance differences across countries.
Argumenta Oeconomica, 2024, Nr 1 (52), s. 145-161